Pacifismo y vínculos transnacionales entre feministas en el continente americano en los años 1930: encontrar una solución a la guerra del Chaco - Maria Elvira Alvarez Gimenez (Les Cahiers ALHIM)
The 1930s were a period of intensified links between feminists in the Americas, particularly in South America, spurred by the Chaco War between Paraguay and Bolivia (1932-1935). Feminists on the continent sought to fight transnationally for women's civil and political rights, but also for the maintenance of peace on the continent. The Pan-American feminist movement thus took on pacifist aims that led women to mobilize through a sort of "informal diplomacy" as soon as the conflict was over, around the issue of the return of prisoners of war. Thanks to the links created between feminists of the continent in these years, a broad transcontinental mobilization of women took place, which placed women and feminists at the forefront of the public sphere in their respective countries.